Effects of long-term phosphorus fertilization and straw incorporation on phosphorus fractions in subtropical paddy soil - Yu-yuan LI; Rui YANG; Ru GAO; Hong-an WEI; An-lei CHEN; Yong LI (Journal of Integrative Agriculture, 2015)
Study on soil phosphorus (P) fraction is an important aspect in probing the mechanisms of soil P accumulation in farmland and mitigating its losing risk to the environment. We used a sequential extraction method to evaluate the impacts of long-term fertilization and straw incorporation on inorganic, organic, and residual P (Pi, Po, and Pre) fractions in the plow layer (0–20 cm) of acidic paddy soil in southern China. The experiment comprised of six treatments: (i) no fertilizer control (CK); (ii) straw incorporation and green manure (SG); (iii) nitrogen and P fertilizer (NP); (iv) NP+SG; (v) NP+K fertilizer (NPK); and (vi) NPK+SG. The results showed that, compared to the initial total soil P content (TSP, 600 mg kg−1 in 1990), long-term (20 years) combined continuous P fertilizer and SG significantly increased P accumulation (by 13–20%) while single fertilization (39.3 kg P ha−1 yr−1) could maintain soil P status at the most. The average soil P fractions comprised of extractable Pi, Po, and Pre by 51.7, 33.4, and 14.9% in total soil P, respectively. With comparison of no fertilizer addition (CK), long-term single fertilization significantly (P<0.05) increased the accumulation of NaHCO3−, NaOH−, and HCl− extractable Pi fractions accounting for two- to three-fold, while SG increased the accumulation of NaHCO3− and NaOH− extractable Pi and Po accounting for 12–60%. Though the mobilization of Pre fractions was not significant (P>0.05), our data indicate that SG may partially substitute for fertilizer P input and minimizing soil P accumulation and subsequent environmental risk in the subtropical paddy soil.